Looking to methods and tools for the Research in Design and Architectural Technology (2015)
The volume presents the research experience of young researchers and PhD candidates, dealing with the Italian scientific area 08-C1 (Design and Technology of Architecture), with a discussion about scientific issues and methodologies applied. The aim is to express the methodological and investigation features of the issues faced by the researchers, along with the effectiveness of their researches design, giving the reader an immediate overview of the 08-C1 doctoral experience. Beside young researchers statements as witnesses of this research path, the volume collects professors critical contribution, to enrich the comprehensive picture of the progression and methodologies of the doctoral researches presented.